Posterior surgical approach and stabilization procedure with “free-hand” technique in a 17-year-old patient with burst type fracture of the L1 vertebra and incomplete spinal cord injury (ASIA Impairment Scale C) - Christopher Lauren; Samuel Edhi Suranta; Elric Brahm Malelak; Donny Argie (Indoscholar, 2020)
Burst type fracture is commonly involved in the thoracolumbar spine, causing a spinal cord injury (SCI). This case represents a 17-year-old female patient presents with a complaint of cannot move both legs and experience a shearing-like pain in the low back. Five days prior, she falls from a 4-meter height abyss, and after that, she cannot move both legs. On the physical examination, both lower extremities muscles are paralyzed, decreased in pain and temperature sensation in both lower extremities, preserved sacral function, and the neurological level of injury (NLI) is located on the L1 vertebra. The American Spinal Injury Association (ASIA) impairment scale is C. The plain X-ray and computed tomography (CT) scan of the thoracolumbar spine show compression of the L1 vertebra and narrowing of the spinal canal caused by retropulsion bone fragment. We treated the patient with laminectomy decompression and posterior stabilization with pedicle screw and rod instrumentation, which is done without the use of a C-arm and performed with a free-hand technique using the anatomical landmark. No complication found with this procedure. After periodically follow up, the neurological examination, either the motoric and sensory function, is improved.